Prevalence and determinants of health literacy among the adult population of Qatar - Ahmed, Salma; Kehyayan, Vahe; Abdou, Mariam; Bougmiza, Iheb (Frontiers in Public Health, 2023)
Introduction Health literacy (HL) is both a direct determinant and a mediator of health outcomes. Research on the prevalence and determinants of HL in terms of its functional, communicative, and critical domains is scarce in the state of Qatar and its surrounding regions. Thus, this study aims to fill the knowledge gap in this area, estimate the levels of functional, communicative, and critical health literacy among the general adult population, and identify its determinants in the state of Qatar. Methods An analytical cross-sectional study with a disproportionate stratified random sampling technique was conducted in 2022. A representative sample of phone numbers was obtained from the Cerner database at Hamad Medical Corporation and approached via well-trained data collectors. A socio-demographic and health-relevant factor questionnaire and the validated All Aspects of Health Literacy scale (AAHLS) were used to collect the data on functional, communicative, and critical HL and their determinants. Descriptive analysis, independent sample t-test, ANOVA, and linear regression were used and yielded the outcomes on HL levels as low, adequate, and high in percentages and the HL determinants. Results A total of 770 participants were included. The study found that 41.5%, 29.3%, and 29.2% of them have adequate, high, and low overall HL levels consecutively. People who participated in the study are older adult, are of Arabic ethnicity, are of Qatari ethnicity, have a lower level of education, have close relatives with a lower level of education, have a lower income, are non-migrants, are not living within a family, sought medical care within the last week, and who do not know if they have a chronic disease or do not have lower overall HL levels compared to the other groups. After linear regression analysis, only the participant's level of education and “last time sought medical care within last week” variable predict the overall HL score. Conclusion Almost half of Qatar's adult population has an adequate HL level, comparable to the HL levels in other regions, despite the limitation in comparison due to variation in context and the HL measurement tools used. The possible determinants are amenable factors to focus on while designing HL interventions and providing healthcare.